GLOBAL AEROSPACE INDUSTRY RISKS - Tomasz BALCERZAK (Scientific Journal of Silesian University of Technology. Series Transport, 2019)
The global Aerospace industry is expected to improve in 2018 as its revenue is predicted to rise by 4.1% , doubling last year’s 2.1% growth. The recovery of global gross domestic product (GDP), stable commodity prices, and increased passenger travel demand are likely to ramp up growth in the commercial aircraft sector in 2018. This article reviews the performance of the aerospace industry in 2017 and 2018 and speculates its growth in the incoming years. It also outlines the performance across the major aerospace markets and discusses trends that will impact the industry. The article forecasts the mergers and acquisitions activity in 2018 that lays the foundation for further growth in this space. Key findings are: - Commercial aircraft sector revenues are expected to grow by 4.8% as production levels are likely to be robust while the defence sector revenues are likely to record 3.6% growth as the US defence budget recovers after experiencing multi-year declines. - The spiralling demand for passenger travel is driving commercial aircraft production and is responsible for the record high backlog of 14,215 units at the end of 2017. • In 2018, global Mergers and Acquisitions (M&A) activity is expected to remain strong in the aerospace sector, being driven by pricing pressures from aircraft OEMs and their expansion of high-margin aftermarket services. This has pushed suppliers to consolidate for scale and cost-effectiveness.